2023
DOI: 10.1002/pd.6329
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐country comparison of pregnant women's decision‐making and perspectives when opting for non‐invasive prenatal testing in the Netherlands and Belgium

Abstract: Background The Netherlands and Belgium have been among the first countries to offer non‐invasive prenatal testing (NIPT) as a first‐tier screening test. Despite similarities, differences exist in counseling modalities and test uptake. This study explored decision‐making and perspectives of pregnant women who opted for NIPT in both countries. Methods A questionnaire study was performed among pregnant women in the Netherlands (NL) (n = 587) and Belgium (BE) (n = 444) opting for NIPT, including measures on inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…While the uptake of NIPT did increase slightly after its introduction, most women still declined prenatal testing 27 . The data gathered from this study as well as from studies in other countries clearly indicate that appropriate counseling is the key to achieving high levels of informed test‐choice decisions rather than the test itself 27–33 …”
Section: The Case In Favormentioning
confidence: 74%
See 1 more Smart Citation
“…While the uptake of NIPT did increase slightly after its introduction, most women still declined prenatal testing 27 . The data gathered from this study as well as from studies in other countries clearly indicate that appropriate counseling is the key to achieving high levels of informed test‐choice decisions rather than the test itself 27–33 …”
Section: The Case In Favormentioning
confidence: 74%
“…27 The data gathered from this study as well as from studies in other countries clearly indicate that appropriate counseling is the key to achieving high levels of informed test-choice decisions rather than the test itself. [27][28][29][30][31][32][33] Another initial fear was that the introduction of NIPT would result in a drastic decrease in the livebirth prevalence of Down syndrome. A register study of the period 2014-2018, which included the start of NIPT as a first-tier test in 2017, concluded this was not the case.…”
Section: Societal and Ethical Aspectsmentioning
confidence: 99%
“…Patients undergoing NIPT represent a population sample, so their genomic data can be valuable for population studies. This is particularly relevant in countries where NIPT has been implemented in public prenatal care, such as the Netherlands and Belgium [ 30 ]. On the samples of pregnant Slovak, Czech, and Hungarian women, we have shown that without additional investment in laboratory consumables, NIPT has the potential to obtain population frequencies of large-scale CNVs.…”
Section: Discussionmentioning
confidence: 99%
“…9,[54][55][56] The majority of pregnant people prefer NIPT to other options due to its superior screening performance, earlier testing, lower risk of requiring an invasive diagnostic test, and fewer anxieties. 57,58 However, NIPT as a primary screen is a more costly strategy than the contingent model. 51,59 Furthermore, if NIPT replaces the nuchal translucency (NT) ultrasound at 11-13 weeks, then its implementation as a primary screen will also reduce opportunities for early ultrasound detection of fetal structural anomalies.…”
Section: Conditionmentioning
confidence: 99%
“…In recent years, several professional society statements have affirmed that NIPT could be offered to pregnant people as a primary screen, with various caveats around funding arrangements and other local access factors 9,54–56 . The majority of pregnant people prefer NIPT to other options due to its superior screening performance, earlier testing, lower risk of requiring an invasive diagnostic test, and fewer anxieties 57,58 . However, NIPT as a primary screen is a more costly strategy than the contingent model 51,59 .…”
Section: Implementation Models Of Non‐invasive Prenatal Testingmentioning
confidence: 99%